2019
DOI: 10.1002/mar.21177
|View full text |Cite
|
Sign up to set email alerts
|

Lost and found: Individual differences in propensity to process visual elements of persuasion

Abstract: Visual processing style, defined as the relative propensity to engage in visual processing rather than verbal processing, is an individual difference variable that has been frequently investigated in the consumer psychology literature. Surprisingly, numerous studies have reported no relationship between visual processing style and viewer responses to visual elements of persuasion. We argue that this accumulation of null results is due to untenable historical theoretical assumptions that underlie the construct,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…However, Townsend and Kahn ( 2014 ) indicate that a content-rich visual presentation may cause a problem of choice overload and thus generate negative consumer responses. Especially, DeRosia and McQuarrie ( 2019 ) find that different propensity of individuals to process visual information (VisProp) will elicit different evaluations of the visual aesthetics toward a visual advertisement. For these reasons, further exploration is needed for the antecedents of visual aesthetics perceptions.…”
Section: Discussionmentioning
confidence: 99%
“…However, Townsend and Kahn ( 2014 ) indicate that a content-rich visual presentation may cause a problem of choice overload and thus generate negative consumer responses. Especially, DeRosia and McQuarrie ( 2019 ) find that different propensity of individuals to process visual information (VisProp) will elicit different evaluations of the visual aesthetics toward a visual advertisement. For these reasons, further exploration is needed for the antecedents of visual aesthetics perceptions.…”
Section: Discussionmentioning
confidence: 99%
“…We did not include studies (a total of 17 studies) that instructed participants specifically to simulate reducing their future consumption behavior (e.g., reducing alcohol consumption; Conroy, Sparks, and De Visser 2015) or that instructed participants to simulate risks, problems, and negative sensory experiences (e.g., consequences of not screening for skin cancer [Block and Keller 1997], potential problems buying really new products [Dahl and Hoeffler 2004], disgust from neglecting gum health [Dillard and Shen 2018]). Studies must have assessed a behavioral response in the form of (1) intentions, (2) choice between two alternatives, (3) actual consumption, or (4) amount of behavior (e.g., exercise). Given that mental simulation affects behavior directly, we did not include studies that solely assessed attitudes toward the brand or the company (e.g., DeRosia and McQuarrie 2019), attitudes toward the advertisement through which mental simulation was encouraged (e.g., Bolls and Muehling 2007), or memory recall (e.g., Klepacz et al 2016). However, we computed attitude effects in studies that assessed attitudes in addition to behavioral responses to test for any evidence of an inference process. Studies needed to have sufficient information (means, standard deviations, F-ratios, t-tests, etc.)…”
Section: Methodsmentioning
confidence: 99%
“…More recently, DeRosia and McQuarrie (2019) reanalyzed past studies focused on investigating style of processing and had concluded a null effect of individual differences in SOP. However, in their paper they proposed a slightly different approach to conceptualizing SOP.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, in their paper they proposed a slightly different approach to conceptualizing SOP. Instead of taking a “relative propensity” view of visual or verbal preference, the authors propose that taking an “absolute” approach to conceptualizing SOP, that is, considering visual and verbal measures separately, overcomes the original assumptions to unbound preference, dominance, and comparison (DeRosia & McQuarrie, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%